Whole exome/genome sequencing in cyclic vomiting syndrome reveals multiple candidate genes, suggesting a model of elevated intracellular cations and mitochondrial dysfunction - Bar, Omri; Ebenau, Laurie; Weiner, Kellee; Mintz, Mark; Boles, Richard G. (Frontiers in Neurology, 2023)
Objective To utilize whole exome or genome sequencing and the scientific literature for identifying candidate genes for cyclic vomiting syndrome (CVS), an idiopathic migraine variant with paroxysmal nausea and vomiting. Methods A retrospective chart review of 80 unrelated participants, ascertained by a quaternary care CVS specialist, was conducted. Genes associated with paroxysmal symptoms were identified querying the literature for genes associated with dominant cases of intermittent vomiting or both discomfort and disability; among which the raw genetic sequence was reviewed. “Qualifying” variants were defined as coding, rare, and conserved. Additionally, “Key Qualifying” variants were Pathogenic/Likely Pathogenic, or “Clinical” based upon the presence of a corresponding diagnosis. Candidate association to CVS was based on a point system. Results Thirty-five paroxysmal genes were identified per the literature review. Among these, 12 genes were scored as “Highly likely” (SCN4A, CACNA1A, CACNA1S, RYR2, TRAP1, MEFV) or “Likely” (SCN9A, TNFRSF1A, POLG, SCN10A, POGZ, TRPA1) CVS related. Nine additional genes (OTC, ATP1A3, ATP1A2, GFAP, SLC2A1, TUBB3, PPM1D, CHAMP1, HMBS) had sufficient evidence in the literature but not from our study participants. Candidate status for mitochondrial DNA was confirmed by the literature and our study data. Among the above-listed 22 CVS candidate genes, a Key Qualifying variant was identified in 31/80 (34%), and any Qualifying variant was present in 61/80 (76%) of participants. These findings were highly statistically significant (p < 0.0001, p = 0.004, respectively) compared to an alternative hypothesis/control group regarding brain neurotransmitter receptor genes. Additional, post-analyses, less-intensive review of all genes (exome) outside our paroxysmal genes identified 13 additional genes as “Possibly” CVS related. Conclusion All 22 CVS candidate genes are associated with either cation transport or energy metabolism (14 directly, 8 indirectly). Our findings suggest a cellular model in which aberrant ion gradients lead to mitochondrial dysfunction, or vice versa, in a pathogenic vicious cycle of cellular hyperexcitability. Among the non-paroxysmal genes identified, 5 are known causes of peripheral neuropathy. Our model is consistent with multiple current hypotheses of CVS.